PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021)” - Faadhil Maajid (Lobi, 2024)
Stock prices are prices as they are on the stock exchange market at a certain moment and are decided by other market participants. The high and low price of these shares is determined by the demand and supply of these shares in the capital market. This study aims to determine the effect of Return on Assets, Return on Equity and Earnings per Share on stock prices. The research method used in this study is to use a verifiative descriptive method with a quantitative approach. The data used in this study is secondary data obtained from the Indonesia Stock Exchange (IDX) website www.idx.co.id. Data collection techniques with indirect collection. The population used is 68 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The selection of samples using the purposive sampling method with data obtained according to predetermined criteria was 15 companies. The data obtained were as many as 75 and analyzed by regression analysis of panel data, simultaneous tests (f tests) and partial tests (t tests). The test results show that Return on Assets does not have a significant effect on Stock Price, Return on Equity has a significant effect on Stock Price and Earnings per Share has a significant effect on Stock Price.